Awareness of Patients’ Rights among Inpatients of a Tertiary Care Teaching Hospital– A Cross-sectional Study - Upasana Agrawal (Journal of Clinical and Diagnostic Research, 2017)
Introduction: The rights of a patient are a set of rules of conduct which govern the interaction between the patients' and healthcare professionals. Every patient has a right to be informed about their rights and also the responsibility of the healthcare provider. Aim: To assess awareness among inpatient about patients' rights at an academic accredited hospital. Materials and Methods: A questionnaire based cross-sectional study was carried out among 350 patients admitted to the wards of a Tertiary Care Teaching Hospital. A 21-point questionnaire was developed based on standards of the National Accreditation Board for Hospitals and Healthcare Providers (NABH) and patients' charter of rights and validated. This charter of rights is also displayed in the hospital for patient’s awareness. Frequencies and percentages were depicted. Chi-square test was used for statistical analysis. Results: Positive awareness among the patients ranged from 28% to 97.4%. Females were more aware of their rights than males for 11 out of the 21 patient rights items. Younger adults were more aware than any other age group participants. Participants who were admitted to wards of higher categories (deluxe rooms) had high degree of awareness about patients’ rights and education. Patients from urban areas and higher educational status were more aware than patients coming from rural areas. Conclusion: The study concludes that effective measures should be taken to improve the overall awareness not only among patients but also among different stakeholders in the healthcare delivery system. Readability of the patients' rights charter with good readability score, developing and distributing patient education materials in simple language about the rights and responsibilities to the patient and their family/relatives during their stay in the hospital or at the time of registration. Continuing nursing and medical education in medical teaching institutions and hospitals should focus on patients' rights and its importance, its need for awareness and its consequences should be taught to students and hospital staff. Patient Right Committee in the hospital should be established for supervision monitoring and observance of patients’ rights.